Efeito da imunização com vacina do antígeno recombinante de superfície SpaA de Erysipelothrix rhusiopathiae : modelo murino - Camillo, Luciana (2015)
The swine erysipelas is a disease caused by the bacterium Erysipelothrix rhusiopathiae, globally distributed. The pig farming is expanding, and pork is the most consumed in the world. Large investments have been made to increase these herds, especially in the search for vaccines. The disease is currently prevented by vaccination of flocks, but the existing formulations (inactive or attenuated pathogen) can aggravate problems of arthritis in these animals. For the development of new vaccines, free of E. rhusiopathiae cells, the protein SpaA (Surface protective antigen A) appears as a major antigen in studies. We evaluate, in mice, the immune response and the efficiency of two formulations based on SpaA antigen, and compared the results obtained with a commercial vaccine prepared with inactivated cells of the pathogen. The formulations used were: a) living cells of recombinant attenuated Salmonella typhimurium - SL3261 expressing SpaA; b) SpaA purified protein and aluminum hydroxide (v/v). After immunization and challenge of the animals, we evaluated production of antibodies (ELISA) and the inflammatory cells profile systemic infection by E. rhusiopathiae. The results showed that the purified antigen can promote 50% protection (with an over-dose challenge 50xDL50) of a virulent E. rhusiopathiae. In the DL50 challenge, we analyze the cellular profile, antibody production, and interleukin dosage. The purified protein vaccine promoted negative modulation of the output inflammatory cells from bone marrow into the blood, compared to only infected group. There was a specific IgG production against rSpaA, and the most antigenic vaccine was the purified protein, compared to commercial vaccine and recombinant Salmonella vaccine. By analysis of interleukins (IL-4 and IL-12) and IgG1 and IgG2a subclasses, we found that vaccines stimulate both the Th1 response as Th2, being observed more likely to Th2 response. Thus, these data suggest that SpaA purified protein is capable of stimulating an immune response with protective character, reducing the risk of secondary impairments like those occurring with the use of inactivated vaccines to pathogens.